1977
DOI: 10.2134/agronj1977.00021962006900040026x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Oxygen and Temperature Effect on Tetany Potential of Three Annual Forage Species1

Abstract: Grass tetany, a metabolic disorder of cattle on pasture, has often been related to low Mg and high K levels, and high K/(Ca+Mg) equivalent ratios in forages. These forage mineral imbalances often occur during wet periods when soil O2 may be low. The effect of 2, 4, 8, 16, and 21% soil air O2, on Ca, Mg, and K contents of rye (Secale cereale L.), ryegrass (Lolium multiflorum Lam.), and arrowleaf clover (Trifolium vesiculosum Savi) was studied in the growth chamber at 22 C day air temperatures and 12 or 16 C nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 4 publications
2
9
0
Order By: Relevance
“…Thus, the only significant alteration in mineral composition observed by us for mature rye plants subjected previously to 2-week oxygen stresses concerns potassium. The decrease in straw-K is in agreement with a K reduction in rye forage at low soil 02, reported by Elkins and Hoveland (1977), whereas Dechnik et al (1985) did not find such a reduction in the same winter rye variety, not even after 4 weeks of flooding. No change in grain-K was observed by us at low ODR values in any of the three study years.…”
Section: Influence Of Oxygen On Growth Of Rye 271supporting
confidence: 88%
See 1 more Smart Citation
“…Thus, the only significant alteration in mineral composition observed by us for mature rye plants subjected previously to 2-week oxygen stresses concerns potassium. The decrease in straw-K is in agreement with a K reduction in rye forage at low soil 02, reported by Elkins and Hoveland (1977), whereas Dechnik et al (1985) did not find such a reduction in the same winter rye variety, not even after 4 weeks of flooding. No change in grain-K was observed by us at low ODR values in any of the three study years.…”
Section: Influence Of Oxygen On Growth Of Rye 271supporting
confidence: 88%
“…Few papers report the response of rye to soil hypoxia. Elkins and Hoveland (1977) found that the concentration of K in rye forage decreased with reduced soil 0 2 while that of Ca and Mg did not change. Dechnik et al (1985) observed an increase in N and a decrease in P and Mg (without an effect on K and Ca) in winter rye grain and an increase in N, Ca and Mg in rye straw associated with up to four weeks of flooding at stem elongation.…”
Section: Introductionmentioning
confidence: 89%
“…However, the Mg content was relatively low (16g/kgDM), possibly due to the waterlogged ground conditions pertaining during an exceptionally wet spring (Elkins and Hoveland, 1977). However, the Mg content was relatively low (16g/kgDM), possibly due to the waterlogged ground conditions pertaining during an exceptionally wet spring (Elkins and Hoveland, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Soil 02 levels often are low during the grass tetany season because soils often are saturated with water. Elkins and Hoveland (1977) showed that low soil 0 2 levels caused a decrease in Mg concentration of annual ryegrass (Lolium multiflorum L.). Haaland et al (1978), in a greenhouse study, examined the effects of low soil 02 levels on Mg concentration in tall fescue and found similar results.…”
Section: Stability Of Genotypes Under Various Conditionsmentioning
confidence: 99%